Structural equation modelling and system dynamic in the detection of power quality events - Azizan, Ashraf Zulfa (2012)
The issues of power quality had been discussed since the starting of power system and it will keep on arise from time to time because power quality is important to electricity consumers at all levels of usage. Since sensitive equipments and power electronic devices are now more common in industrial/commercial sectors as well as domestic use, the awareness of power quality is developing amongst electricity users. In general, the main power quality issues can be identified as voltage variations, voltage imbalance, voltage fluctuations, transients, harmonic distortions, interruptions, etc. The consequences of one or more of the above non-ideal conditions may cause thermal effects, life expectancy reduction, dielectric strength reduction and disoperation of different equipments. In this project, power quality events are verified using Structural Equation Modeling (SEM) and System Dynamic method. In detecting power quality events, Amos 5.0.1 and Vensim PLE for Windows version 5.11 were used. The verification of power quality events involves identification, classification and mitigation process on several power quality events that occurred in electrical power system.